2019
DOI: 10.1158/1078-0432.ccr-18-2380
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine–Mediated Tumor Cell Protection and Poor Patient Survival Associated with OCTN2 Overexpression in Glioblastoma Multiforme

Abstract: Purpose: Apoptotic dysregulation, redox adaptive mechanisms, and resilience to hypoxia are major causes of glioblastoma (GBM) resistance to therapy. Commonly known as crucial factors in energy metabolism, OCTN2 (SLC22A5) and its substrate L-carnitine (LC) are increasingly recognized as actors in cytoprotection. This study provides a comprehensive expression and survival analysis of the OCTN2/LC system in GBM and clarifies the system's impact on GBM progression.Experimental Design: OCTN2 expression and LC conte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…To date, several studies reported a link between the altered expression of OCTN2 and cancer development and progression (Lu et al, 2008;Scalise et al, 2012;Wang et al, 2012;Elsnerova et al, 2016;Lee et al, 2016;Fink et al, 2019;Juraszek and Nalecz, 2019; Table 1). Interestingly, its expression is found up or down-regulated depending on the carbon source that the tumors use to produce energy.…”
Section: Implications Of Octn2 In Cancermentioning
confidence: 99%
“…To date, several studies reported a link between the altered expression of OCTN2 and cancer development and progression (Lu et al, 2008;Scalise et al, 2012;Wang et al, 2012;Elsnerova et al, 2016;Lee et al, 2016;Fink et al, 2019;Juraszek and Nalecz, 2019; Table 1). Interestingly, its expression is found up or down-regulated depending on the carbon source that the tumors use to produce energy.…”
Section: Implications Of Octn2 In Cancermentioning
confidence: 99%
“…Interestingly, the fatty acid oxidation enzymes (including CPT1a) were also detected in glioma cells and the process of fatty acid oxidation contributed significantly to their aerobic respiration, while treatment with etomoxir decreased cell proliferation and prolonged survival in the mouse model of this disease [88]. Moreover, OCTN2 expression was increased in primary glioblastoma samples from patients, and even more so in samples from patients with recurrent glioblastoma, when compared to the healthy brain [89].…”
Section: Slc22a5 and Fatty Acid Oxidation In Cancermentioning
confidence: 99%
“…A deeper knowledge of the biological basis of the antitumor effects of δVB is tempting, especially in light of the possible mechanism of action of δVB occurring through the reduction of l-carnitine uptake by inhibiting the organic l-carnitine cation transporter type 2 [12], known to have an altered expression in several cancer cell lines. In particular, this mechanism may take part to an alternative to glucose source of energy for cancer cells growth and proliferation by supplying l-carnitine for β-oxidation [23,24]. The present study aimed at evaluating the possible anticancer effects of milk betaines in oral squamous cell carcinomas [25].…”
Section: Introductionmentioning
confidence: 99%